Hydrogen Bonding as a Supramolecular Tool for Robust OFET Devices1. Issue 35 (27th May 2019) - Mula, Soumyaditya; Han, Tianyan; Heiser, Thomas; Lévêque, Patrick; Leclerc, Nicolas; Srivastava, Amit Prakash; Ruiz‐Carretero, Amparo; Ulrich, Gilles
Abstract: In the present study, we demonstrated the effect of hydrogen bonding in the semiconducting behaviour of a small molecule used in organic field‐effect transistors (OFETs). For this study, the highly soluble dumbbell‐shaped molecule, Boc‐TATDPP based on a Boc‐protected thiophene‐diketopyrrolopyrrole (DPP) and triazatruxene (TAT) moieties was used. The two Boc groups of the molecule were removed by annealing at 200 °C, which created a strong hydrogen‐bonded network of NH‐TATDPP supported by additional π–π stacking. These were characterised by thermogravimetric analysis (TGA), UV/Vis and IR spectroscopy, XRD and high‐resolution (HR)‐TEM measurements. FETs were fabricated with the semiconducting channel made of Boc‐TATDPP and NH‐TATDPP separately. It is worth mentioning that the Boc‐TATDPP film can be cast from solution and then annealed to get the other systems with NH‐TATDPP. More importantly, NH‐TATDPP showed significantly higher hole mobilities compared to Boc‐TATDPP. Interestingly, the high hole mobility in the case of NH‐TATDPP was unaffected upon blending with [6, 6]‐phenyl‐C71‐butyric acid methyl ester (PC71 BM). Thus, this robust hydrogen‐bonded supramolecular network is likely to be useful in designing efficient and stable organic optoelectronic devices. Abstract : Successful networking : A Hydrogen‐bonded supramolecular network enhances the hole mobility in organic field‐effect transistors (OFETs) by two orders of magnitude as compared to its parent compound (see figure).